Total ionizing dose influence on proton irradiated triple gate SOI tunnel FETs - Torres, H. L.F.; Martino, J. A.; Rooyackers, R.; Simoen, E.; Claeys, C.; Agopian, P. G.D. [UNESP] (Journal of Integrated Circuits and Systems, 2018)
This paper reports an analysis of radiation ef-fects on triple gate SOI tunnel FETs from a total ionizing dose point of view, based on measurements and TCAD simu-lations. Devices with different dimensions were exposed to a dose of 1 Mrad(Si) generated by a 600 keV proton radiation source. It was possible to notice a drain current decrease for irradiated devices that reduces with increasing channel length and gate bias. To explain this behavior, the influence of positive charges at front and back interfaces generated by the cumulative exposure to radiation was analyzed, as well as devices’ internal characteristics for such operation condi-tions. This analysis is based on the competition between a high channel resistance present in longer devices and the TFET drain current reduction due to the irradiation.
Keywords: Proton radiation; SOI; TCAD simulation; TFET; TID